Fração Enriquecida em proantocianidinas de Stryphnodendron adstringens (Mart.) coville: atividade em linhagens celulares de câncer cervical, tumor sólido de Ehrlich e ensaio clínico fase I - Kaplum, Vanessa (2018)
Cervical cancer is the fourth most common cancer that affects women worldwide, mainly through human papiloma virus (HPV) infection with high-risk HPV16 and HPV18. The drugs available for the cancer treatment do not always reach the expected therapeutic effects, so it is imperative to search for new alternatives. Furthermore, therapeutic alternatives must be safe for human use. The present study investigated the in vitro anticancer activity and mechanism of action of a proanthocyanidin polymer-rich fraction of Stryphnodendron adstringens (F2) in cervical cancer cell lines, including HeLa (HPV18-positive), SiHa (HPV16positive), and C33A (HPV-negative) cells, as well as the in vivo antitumor activity, and the safety for humans. Cell viability was determined by the MTT assay. Cell migration was determined by the wound healing assay. The mechanism of action was investigated by performing ultrastructural analysis and evaluating reactive oxygen species (ROS) production, reduced thiol levels, mitochondrial metabolism, BCL-2 family expression, caspase expression, lipoperoxidation, DNA and cell membrane integrity. In vivo activity was evaluated using the murine Ehrlich solid tumor model. The safety of intravaginal gel containing 5% of F2 was evaluated by a clinical trial Phase I. Proanthocyanidin polymer-rich fraction of S. adstringens time- and dose-dependently reduced cell viability of HeLa, SiHa and C33A cells, and significantly inhibited the migration of cervical cancer cells. In the HeLa and SiHa cells (IC50) there were intense oxidative stress due to increase in ROS and depletion of reduced thiol levels. Treatment with F2 also induced mitochondrial damage sufficient to trigger mitochondriadependent apoptosis, such as mitochondrial membrane potential depolarization, reduction of intracellular levels of ATP, and increase in Bax-BCL-2 ratio, associated with an increase in caspase 9 and 3 expression, and DNA damage. In C33A cells treated with IC50 and IC90, and HeLa and SiHa cells treated with IC90 of F2 also there were increase in lipoperoxidation and cell membrane disruption, indicating progress to late apoptosis/necrosis. The inhibition of ROS production by N-acetylcysteine significantly suppressed oxidative stress in all three cell lines. In the murine Ehrlich solid tumor model, there was a significant decrease in the tumor volume and weight after treatment with F2. Also, significantly increased lipoperoxidation in the tumor indicating that F2 also induces oxidative stress in the in vivo model. Clinical trial Phase I showed that the intravaginal gel containing 5% of F2 was safe and well tolerated, without relevant systemic or local alterations in the parameters evaluated. These findings indicate that the proanthocyanidin polymer-rich fraction of S. adstringens may be a potential chemotherapeutic candidate for cervical cancer treatment